Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon